Evaliuation of aqueous extract of red and yellow allium cepa (onion) against pathogenic bacterial assosiated with ocular infections / Muhamad Khairul Amirin Zulkifli - Zulkifli, Muhamad Khairul Amirin (2017)
The emergence of antibiotic resistance in pathogenic bacteria has led to changed interest in exploring the potential of natural resources as an alternative therapeutic strategy to combat microbial infections. The present study was conducted to evaluate the antimicrobial activity of aqueous extract of red and yellow Allium cepa (A. cepa) bulbs (onion) against Staphylococcus aureus (S. aureus), Bacillus cereus (B. cereus), Esherichia coli (E. coli) and Pseudomonas aeruginosa (P. aeruginosa). Antimicrobial susceptibility testing (AST) by disc diffusion method and minimum inhibitory concentration (MIC) by using the microdilution broth method was performed. The results of AST showed that the A. cepa extract has the highest inhibiting effect against S. aureus (16mm) for red A. cepa and 11mm for yellow A. cepa, while the extract showed little effect against E.coli where 9mm for red A. cepa and 7 for yellow A. cepa while for B. cereus there were the same diameter for AST (11mm). There is no zone of inhibition against P. aeruginosa. The result of MIC value showed the minimum concentration of A. cepa aqueous extract to inhibit the S. aureus (red=125mg/ml, yellow= 250mg/ml) B. cereus (red=62.5mg/ml, yellow= 250mg/ml) and E.coli (red=62.5mg/ml, yellow= 250mg/ml). The study managed to prove that red and yellow aqueous extract of A. cepa has potential to be used as natural antimicrobial agent.